2008
DOI: 10.1016/j.neurobiolaging.2006.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Physiological correlates of age-related decline in vibrotactile sensitivity

Abstract: The purpose of this study was to describe age-related changes in vibrotactile sensitivity in participants of the Baltimore Longitudinal Study of Aging and to identify factors that are associated with impairment in vibrotactile sensitivity independent of age. Participants (n=523, age:26-95 years) underwent measurements of vibration perception threshold (VPT, 100Hz) under the 2 nd metatarsal head, glucose tolerance, serum inflammatory markers, nerve conduction parameters, movement time and cognition. Univariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 32 publications
4
36
1
8
Order By: Relevance
“…Likewise, Maurissen and Chrzan did not obtain significant findings in their studies on VPTs measured at 150 Hz in 29 women with finger skin temperature ranging from 23.6°C to 35.3°C (mean: 34°C) [26]. Researchers investigating the possible influence of skin temperature on VPT among healthy subjects should consider a number of individual characteristics such as age, gender and BMI, that can affect the study results [27][28][29]. The presence of 2 different individual features in a given study group may bring about a diverse impact on VPT.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Maurissen and Chrzan did not obtain significant findings in their studies on VPTs measured at 150 Hz in 29 women with finger skin temperature ranging from 23.6°C to 35.3°C (mean: 34°C) [26]. Researchers investigating the possible influence of skin temperature on VPT among healthy subjects should consider a number of individual characteristics such as age, gender and BMI, that can affect the study results [27][28][29]. The presence of 2 different individual features in a given study group may bring about a diverse impact on VPT.…”
Section: Discussionmentioning
confidence: 99%
“…This decline appears to be similar in men and women (18) and is steeper for vibration than other sensory modalities, such as touch (19). The literature for gender differences in somatosensory function is less clear.…”
Section: Age and Gender Differencesmentioning
confidence: 92%
“…It has been demonstrated that the length or peripheral nerves can influence sensitivity to tactile responses such as vibration perception [4134,4235]. However if this were to be true for thermal sensitivity one would expect to see a proximal to distal decline in thermal sensitivity across the body.…”
Section: Effect Of Ageing and Regional Differencesmentioning
confidence: 99%